Differing physiological adaptations induced by dry and humid short-term heat acclimation - Tebeck, S. T.; Buckley, J. D.; Bellenger, C. R.; Stanley, J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the effect of a 5-day short-term heat acclimation (STHA) protocol in dry (43°C and 20% relative humidity) or humid (32°C and 80% relative humidity) environmental conditions on endurance cycling performance in temperate conditions (21°C). Methods: In a randomized, cross-over design, 11 cyclists completed each of the two 5-day blocks of STHA matched for heat index (44°C) and total exposure time (480 min), separated by 30 days. Pre- and post-STHA temperate endurance performance (4-min mean maximal power, lactate threshold 1 and 2) was assessed; in addition, a heat stress test was used to assess individual levels of heat adaptation. Results: Differences in endurance performance were unclear. Following dry STHA, gross mechanical efficiency was likely reduced (between-condition effect size dry vs humid -0.59; 90% confidence interval, -1.05 to -0.15), oxygen uptake was likely increased for a given workload (0.64 [0.14 to 1.07]), and energy expenditure likely increased (0.59 [0.17 to 1.03]). Plasma volume expansion at day 5 of acclimation was similar (within-condition outcome 4.6% [6.3%] and 5.3% [5.1%] dry and humid, respectively) but was retained for 3 to 4 days longer after the final humid STHA exposure (-0.2% [8.1%] and 4.5% [4.2%] dry and humid, respectively). Sweat rate was very likely increased during dry STHA (0.57 [0.25 to 0.89]) and possibly increased (0.18 [-0.15 to 0.50]) during humid STHA. Conclusion: STHA induced divergent adaptations between dry and humid conditions, but did not result in differences in temperate endurance performance.